Modern architecture international style - Burgos F., Johnny (Revista Universidad de Guayaquil, 2015)
Define the practice of contemporary architecture in the twenty-first century, it requires several readings which would put the various proposals and study them and to try to recognize languages and trends, see new signs schemes or just new space proposals. A reading of contemporary architecture requires diverse knowledge, new epistemologies and new codes of reading and interpretation. It is necessary that these new sources recourse, new signs and new codes, new languages Ultimately create new ways of reading. This paper intends to initiate a new way of interpretation